Cytochalasans from the endophytic fungus Diaporthe ueckerae associated with the fern Pteris vittata. (October 2022) - Gao, Suying; Wu, Ping; Xue, Jinghua; Li, Hanxiang; Wei, Xiaoyi
Abstract: Six previously undescribed cytochalasans, ueckerchalasins A−E and 4′-hydroxycytochalasin J3, together with eight known congeners, were isolated from solid cultures of the endophytic fungus Diaporthe ueckerae SC-J0123 which was originally isolated from the leaves of Pteris vittata L. Their structures were elucidated by extensive spectroscopic analysis, single-crystal X-ray diffraction, and theoretical simulations of ECD spectra and 13 C NMR shifts. Ueckerchalasins A–C have a carbon-carbon bridge between C-14 and C-20, forming a rare 5/6/6/7-fused heterocyclic core. Ueckerchalasins C and D displayed selective activity against human carcinoma HeLa and HepG2 cells. Ueckerchalasins C was also active against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Graphical abstract: Six undescribed cytochalasans, including ueckerchalasins A–C with an unusual tetracyclic skeleton, were isolated from a Pteris vittata leaf-derived Diaporthe ueckerae endophyte. Ueckerchalasins C and D were selectively active against carcinoma HeLa and HepG2 cells and ueckerchalasin C was also active against Staphylococcus aureus and MRSA. Image 1 Highlights: Six undescribed cytochalasans from a Pteris vittata leaf-derived Diaporthe ueckerae endophyte. Ueckerchalasins A–C possess an unusual tetracyclic skeleton. Ueckerchalasins C and D were selectively active against carcinoma HeLa and HepG2 cells. Ueckerchalasin C was also active against Staphylococcus aureus and MRSA.